Depletion driven self-assembly of block copolymer solutions by homopolymers. Issue 4 (15th January 2019) - Yang, Tao; Lei, Zhen; Yang, Shuang; Chen, Er-Qiang
Abstract : The addition of a non-adsorbing homopolymer to a block copolymer solution provides a convenient strategy for regulating its self-assembly. Abstract : The addition of a non-adsorbing homopolymer to a block copolymer solution provides a convenient strategy for regulating its self-assembly. We systematically investigate the depletion effect from a homopolymer on the morphologies of AB diblock and BAB triblock copolymers in selective solvents. Increasing the homopolymer content results in larger spherical micelles, and the curvature of micelles is proportional to the square of homopolymer concentrations. A high enough homopolymer concentration may transfer micelles into vesicles. A deep analysis shows that the depletion effect produces attractive interaction between hydrophilic B blocks as well as their contraction on the micellar surface. The size of triblock copolymer micelles is not affected by homopolymers significantly, and spherical-to-wormlike micelle transition occurs at high homopolymer contents. These results have important applications for the precise design of self-assembled nanostructures of copolymer systems.